Mobilization of Cardiovascular Function at Onset of Dosed Aerobic and All-Out Anaerobic Workouts (Baltic Journal of Sport and Health Sciences, 2018)
The objective of this study was to compare the peculiarities in the mobilization of cardiovascular function at the onsetof an exercise test in dependence on age and the type of adaptation to physical loads. The study’s participants were boysof 11, 12, 13 and 14 years old and adults, i. e. 17 voluntary students who were not engaged in sports training and well-trained athletes (all participants were members of various national teams), i. e. 23 athletes in the endurance group, 19 —in the sprint group and 21 — in the combative sports group (box, judo and wrestling). The subjects underwent:1) Roufier’s test (30 squats per 45 seconds); 2) a 30-second duration maximal vertical jump test. A computerizedelectrocardiogram (ECG) system “Kaunas-Load” was employed for the 12-lead ECG recording and analysis during theperformance of workloads. A computerized program allowed to measure the ratio of JT and RR intervals (JT / RR) andthe velocity of adaptation of cardiovascular system to exercise, i.e. the index of velocity of adaptation (V Ad ), by calculationthe difference between the relative changes of JT and RR intervals as a difference: V Ad . = (Jt i  / JT 0 ) 100% – (Rr i  / RR 0 ) 100%. The results obtained during the study allowed to conclude that faster adaptation at the onset of the exerciseis rather characteristic for younger persons but the type of the exercise performed during the long term training processplays a significant role in the developing and improving the velocity of adaptation of cardiovascular system. A fasteradaptation at the onset of the exercise is a more characteristic feature for the trained athletes in sprint events andcombative sports than the representatives of the endurance group or non-athletes. One of the effects of long termadaptation to exercise is a smaller mobilization of cardiovascular system at the onset of the dosed aerobic and all-outanaerobic exercise and the endurance exercise has the most influence on it.Keywords: cardiovascular system, adaptation, exercise test.